2000
DOI: 10.1034/j.1600-0420.2000.078003348.x
|View full text |Cite
|
Sign up to set email alerts
|

Ocular manifestations of incontinentia pigmenti

Abstract: ABSTRACT.Purpose: The study aimed to evaluate the ocular manifestations in patients with incontinentia pigmenti (IP). Methods: Thirty patients from different parts of Sweden participated. Orthoptic and ocular examinations were performed as well as evaluation of refraction and visual acuity. Results: Ocular manifestations, probably associated with IP, were found in 77% (23/30) of the patients. Thirteen had serious or vision-threatening eye manifestations in one eye, of whom 7 were totally blind in that eye from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
75
1
10

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(90 citation statements)
references
References 21 publications
3
75
1
10
Order By: Relevance
“…Holmstrom and Thoren (1) reported ocular findings in 77% patients in their series of 30 patients. These authors identified two groups of patients: one with serious manifestations (43% patients) and one with minor ocular changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Holmstrom and Thoren (1) reported ocular findings in 77% patients in their series of 30 patients. These authors identified two groups of patients: one with serious manifestations (43% patients) and one with minor ocular changes.…”
Section: Discussionmentioning
confidence: 99%
“…It is inherited as an X-linked dominant condition and is fatal in males (1) . Diagnosis is made on the basis of skin biopsy.…”
Section: Introductionmentioning
confidence: 99%
“…techniques as xenon laser photocoagulation or cryosurgery could be used in retinal affections [2]. Seizures should be treated with anticonvulsants.…”
Section: Discussionmentioning
confidence: 99%
“…Figura 2: Retinografia revelando áreas de hipopigmentação com focos de hiperplasia do epitélio pigmentado da retina em ambos olhos microftalmia, catarata, pigmentação conjuntival, alterações corneanas, hipoplasia iriana, uveíte, nistagmo, estrabismo e miopia (3) . O objetivo desse trabalho é relatar um caso de Síndrome de Incontinentia Pigmenti com alterações retinianas importantes, suas características clínicas, diagnóstico e acompanhamento.…”
Section: Figura 1: Dentes Malformadosunclassified
“…Manifestações dentárias ocorrem em 65% dos casos, e inclui anodontia, dentição atrasada e dentes malformados. Porém, os distúrbios visuais e neurológi-cos são os aspectos mais significantes na doença (3) . Manifestações oculares, geralmente assimétricas, são descritas em 35% dos casos.…”
unclassified